Analisa Hubungan Nilai Indeks Sistem Pemerintahan Berbasis Elektronik Terhadap Jumlah Kasus Web-Defacement Menggunakan Regresi Linear - Nugroho, Agung; Achmad Farid Wadjdi; Teddy Mantoro (CSRID (Computer Science Research and Its Development Journal), 2024)
The government has established an electronic-based government system (SPBE) program to realize clean, effective, transparent and accountable government governance as well as quality and trustworthy public services implemented with the principles of effectiveness, integration, continuity, efficiency, accountability, interoperability and security. . The implementation of SPBE has been evaluated with the achievement of 16 government agencies receiving a very good title in monitoring and evaluating the implementation of the Electronic Based Government System (SPBE) in 2022. During 2022, there were several agencies with excellent predicates who reported cases of web defacement in their electronic systems. via the zone-h.org site as an open publication media regarding web defacement cases. The National Cyber and Crypto Agency (BSSN) said that during 2022 there would be 2,348 cases of web defacement with the sector most affected by web defacement attacks being the Government Administration sector with a total of 885 cases. This research analyzes the influence between the SPBE index value as the independent variable and the number of web defacement cases as the dependent variable using a simple linear regression statistical method to see the gap in the relationship between the SPBE index and cyber attack cases in the form of web defacement cases that occurred at SPBE agencies. The research was carried out using quantitative research methods to process research data using a simple linear regression method. In the research, the results showed that F count = 2,363978 < from F table = 4,60011 , so it was concluded that there was no relationship between the SPBE index value and the number of web defacement cases in agencies that received excellent predicate